Tuning of terahertz resonances of pyridyl benzamide derivatives by electronegative atom substitution - Dash, Jyotirmayee (Journal of Infrared, Millimeter, and Terahertz Waves, 2018)
N-(pyridin-2-yl) benzamide (Ph2AP)-based organic molecules with prominent terahertz (THz) signatures (less than 5 THz) have been synthesized. The THz resonances are tuned by substituting the most electronegative atom, fluorine, at ortho (2F-Ph2AP), meta (3F-Ph2AP), and para (4F-Ph2AP) positions in a Ph2AP molecule. Substitution of fluorine helps in varying the charge distribution of the atoms forming hydrogen bond and hence strength of the hydrogen bond is varied which helps in tuning the THz resonances. The tuning of lower THz resonances of 2F-Ph2AP, 3F-Ph2AP, and 4F-Ph2AP has been explained in terms of compliance constant (relaxed force constant). Four-molecule cluster simulations have been carried out using Gaussian09 software to calculate the compliance constant of the hydrogen bonds. Crystal structure simulations of the above molecules using CRYSTAL14 software have been carried out to understand the origin of THz resonances. It has been observed that THz resonances are shifted to higher frequencies with stronger hydrogen bonds. The study shows that 3F-Ph2AP and 4F-Ph2AP have higher hydrogen bond strength and hence the THz resonances originating due to stretching of intermolecular hydrogen bonds have been shifted to higher frequencies compared to 2F-Ph2AP. The methodology presented here will help in designing novel organic molecules by substituting various electronegative atoms in order to achieve prominent THz resonances.
Keywords: Compliance constant; Density functional theory; Ph2AP molecule; Terahertz spectroscopy

Fine-tuning of Terahertz resonances in hydrogen-bonded organic molecular complexes - Dash, Jyotirmayee; Ray, Shaumik; Devi, Nirmala; Basutkar, Nitin; Ambade, Ashootosh V.; Pesala, Bala (Journal of Molecular Structure, 2019)
Novel organic molecular complexes have been designed and synthesized to obtain prominent Terahertz (THz) resonances in the low-frequency region. Intermolecular hydrogen bonds give rise to low-frequency THz resonances and hence binary organic molecular complexes of pyridyl alkylamide/benzamide (DAP) and hexyl thymine (C6THY) with multiple strong intermolecular hydrogen bonds (N-H–-O and N-H–-N) are designed and synthesized. THz resonances of the complexes are fine-tuned by varying the number of benzene rings in the DAP moiety (PrDAP + C6THY, PrPhDAP + C6THY and PhDAP + C6THY). DFT simulation studies of two molecule clusters have been carried out to understand the origin of low-frequency THz resonances. It has been observed that the lowest THz resonances (< 2 THz) originate due to translation/rotation of the whole crystal structure and the resonances from 2 to 4 THz are mainly due to intermolecular hydrogen bond bending/stretching vibrations. In order to understand the individual hydrogen bond strengths, compliance constants, which are inverse of the force constants are calculated and Natural Bond Orbital (NBO) analysis has been carried out. Comparison of the experimental THz spectra of different complexes shows that there is a small but tunable variation in THz resonances from one complex to another. Tuning of THz resonances has potential applications in designing THz tags, which can be used in various anti-counterfeiting applications such as currency notes, pharmaceutical tablets. (C) 2019 Elsevier B.V. All rights reserved.
Keywords: Compliance constant; Natural bond orbital analysis; Organic molecular complex; Terahertz spectroscopy